2022
DOI: 10.3390/jcm11030546
|View full text |Cite
|
Sign up to set email alerts
|

3D Stereophotogrammetric Quantitative Evaluation of Posture and Spine Proprioception in Subacute and Chronic Nonspecific Low Back Pain

Abstract: The literature shows that low back pain causes a reduced lumbar range of movement, affecting patients′ proprioception and motor control. Nevertheless, studies have found that proprioception and motor control of the spine and posture are vague and individually expressed even in healthy young adults. This study aimed to investigate the standing posture and its modifications induced by an instinctive self-correction manoeuvre in subacute and chronic nonspecific low back pain (NSLBP) patients to clarify how NSLBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Floppy test: a transitive (tool-related) test measuring dexterity, which required participants to insert fourteen floppy disks one at a time in the proper case with one hand, as fast as possible, while the other hand controlled the case 29 ; one familiarization trial and two effective trials for each hand (best ones were registered) as shown in figure 4. 30 , which integrates an optoelectronic stereophotogrammetric system, a baropodometric treadmill and a telemetric surface electromyographic device (SEMG) Patients with a UPXB were subjected to a multifactorial analysis of posture and movement, integrating full 3D synchronized skeletal kinematics (including the spine), baropodometric assessments and electromyographic data. To describe trunk and global unbalancing, spinal offset, and global offset (i.e., displacements of each spine markers with respect to the vertical line passing through the S3 vertebra and with respect to the vertical line passing through the middle point between the heels, respectively) are used.…”
Section: Fine Motor Skills Evaluationsmentioning
confidence: 99%
“…Floppy test: a transitive (tool-related) test measuring dexterity, which required participants to insert fourteen floppy disks one at a time in the proper case with one hand, as fast as possible, while the other hand controlled the case 29 ; one familiarization trial and two effective trials for each hand (best ones were registered) as shown in figure 4. 30 , which integrates an optoelectronic stereophotogrammetric system, a baropodometric treadmill and a telemetric surface electromyographic device (SEMG) Patients with a UPXB were subjected to a multifactorial analysis of posture and movement, integrating full 3D synchronized skeletal kinematics (including the spine), baropodometric assessments and electromyographic data. To describe trunk and global unbalancing, spinal offset, and global offset (i.e., displacements of each spine markers with respect to the vertical line passing through the S3 vertebra and with respect to the vertical line passing through the middle point between the heels, respectively) are used.…”
Section: Fine Motor Skills Evaluationsmentioning
confidence: 99%
“…Similar to the transformation of sensor positions described in Section 2.2, the landmark coordinates were transformed relative to the centre of the middle pixel of each US volume (L US,w pos k ) and further transformed to metric units (mm) using defined US voxel spacing. The homogeneous transformation NDI T US obtained in Section 2.2 was reapplied to the US-derived landmarks to determine their location in the NDI coordinate system according to Equation (5).…”
Section: Identification and Validation Of Landmarks In Different Conf...mentioning
confidence: 99%
“…Currently, optoelectronic approaches are considered the gold standard for characterising gross spinal motion of the lumbar and/or thoracic spine [1]. Typically, markers are attached to the skin covering bony landmarks of the spine [2][3][4][5] and thorax [6,7]. The position of individual vertebrae and their reciprocal angles is currently estimated as constant (population-based) fractions of the measured entire lumbar and/or thoracic segment angles using musculoskeletal models [8][9][10], recently reviewed in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, optoelectronic approaches are considered the gold standard for characterising gross spinal motion of the lumbar and/or thoracic spine [1]. Typically, markers are attached to the skin covering bony landmarks of the spine [2][3][4][5] and thorax [6,7]. The position of individual vertebrae and their reciprocal angles is currently estimated as constant (population-based) fractions of the measured entire lumbar and/or thoracic segment angles using musculoskeletal models [8][9][10], recently reviewed in Alemi et al [11].…”
Section: Introductionmentioning
confidence: 99%